A case report on IDH-mutant astrocytoma, CNS WHO grade 4: multi-omic characterization of untreated clinical progression - Tang, Xiaoqin; Wei, Wei; Huang, Yanyan; Zheng, Yi; Xu, Yajing; Li, Fei (Frontiers in Oncology, 2025)
BackgroundThe natural history of untreated IDH-mutant astrocytoma, CNS WHO grade 2, progressing to astrocytoma grade 4 remains poorly characterized.MethodsA 67-year-old woman with a histologically confirmed grade 2 astrocytoma developed a spatially adjacent grade 4 lesion after eight years without therapeutic intervention. Tumor tissue and peripheral blood were analyzed using integrated genomic, transcriptomic, and immune profiling.ResultsThe central region retained grade 2 histology, while the peripheral region exhibited grade 4 features. Both shared mutations in IDH1, TP53, and ATRX, with highly concordant methylation patterns. The grade 4 lesion uniquely acquired mutations in CIC, BRCA2, and RPA4, and showed a 70% increase in NAF1 mutant allele frequency. Pathway analysis revealed MSP-RON and NF-κB activation, increased mast cell infiltration, and reduced IL-17 signaling, dendritic cells, and CD4+/CD8+ T-cell presence. Among the 1,926 peripheral blood T-cell receptor clonotypes, only 2.1% were detected in the tumor regions. Two highly abundant clonotypes were consistently present in peripheral blood, grade 2, and grade 4 samples, indicating clonal persistence across compartments.ConclusionThis case highlights the clonal progression of an IDH-mutant astrocytoma from grade 2 to grade 4, potentially driven by additional mutations and immune remodeling. These exploratory findings suggest candidate mechanisms of glioma evolution and may inform adoptive T-cell therapy approaches.